2018
DOI: 10.4103/0366-6999.226077
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Membranaceus Improving Asymptomatic Left Ventricular Diastolic Dysfunction in Postmenopausal Hypertensive Women with Metabolic Syndrome

Abstract: Background:Postmenopausal women with metabolic syndrome (MetS) have increased cardiovascular morbidity and left ventricular diastolic dysfunction (LVDD). The various protective effects of astragalus membranaceus (AM) have been described in previous studies. Therefore, this study aimed to evaluate the effects of different doses of AM on diastolic function in postmenopausal hypertensive women with MetS.Methods:This was a prospective, randomized controlled study. The postmenopausal hypertensive patients with MetS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…[ 10 , 11 , 20 ] However, MetS may have both time and ethnic differences. [ 9 ] In this study, the prevalence of MetS was observed to increase with time, and the rate was similar to that reported by other studies, [ 5 , 6 , 14 , 15 , 21 , 22 ] especially those comprising a Chinese study population. [ 13 , 23 ] Furthermore, obvious increasing trends were observed for abnormal HDL and FBG.…”
Section: Discussionsupporting
confidence: 89%
“…[ 10 , 11 , 20 ] However, MetS may have both time and ethnic differences. [ 9 ] In this study, the prevalence of MetS was observed to increase with time, and the rate was similar to that reported by other studies, [ 5 , 6 , 14 , 15 , 21 , 22 ] especially those comprising a Chinese study population. [ 13 , 23 ] Furthermore, obvious increasing trends were observed for abnormal HDL and FBG.…”
Section: Discussionsupporting
confidence: 89%
“…Panax pseudoginseng Wall is rich in saponins, volatile oil, and polyacetylenes, which has a good protective effect on the cerebrovascular system ( Liu G. et al, 2020 ). Recently, some well-controlled clinical trials have proved the cardiovascular protection of Astragalus mongholicus Bunge and its extraction ( Piao and Liang, 2014 ; Li et al, 2018 ). Astragalus armour glycosides (ASG) is one of the active ingredients with high content in the Astragalus membranaceus .…”
Section: Discussionmentioning
confidence: 99%
“…In improving the quality of life of patients with chronic heart failure, the effectiveness of AM granules showed a dose-dependent trend ( Yang et al, 2011 ). A prospective randomized controlled study showed that conventional drugs plus AM capsules improved left ventricular diastolic function in hypertensive women with postmenopausal metabolic syndrome ( Li et al, 2018 ). Tian et al(2016) demonstrated that AM injection or AM water decoction can be used as adjuvant therapy for T2DM based on a preliminary meta-analysis.…”
Section: Clinical Studymentioning
confidence: 99%
“…PG2 is an insoluble polysaccharide extracted from Astragalus membranaceus. Li et al (2018) studied the effect of PG2 on patients with spontaneous acute cerebral hemorrhage. The results showed that PG2 administration for 2 weeks did not increase the percentage of Glasgow Outcome Scale (4-5 scores) and Good Mrs Scores (0–2 scores), nor did it produce any anti-inflammatory properties.…”
Section: Clinical Studymentioning
confidence: 99%